Effect of the Milling Parameters on the Characteristics of Ti-50%Al Nanocrystallite Synthesized by Mechanical Alloying (MA) - Al-Dabbagh, Jinan B.; M., Ishak; Rozman, Mohd Tahar; Siti Aisyah, Harun (ESRSA Publications Pvt. Ltd., 2013)
Titanium aluminide nano alloys has been successfully produced by mechanical alloying (MA) technique in a planetary ball mill and followed by subsequent heating. The influence of milling parameters such as the milling duration, rotation speed and balls to powder mass ratio on the characteristics of the Ti50%Al powder including the micro structural, crystallite size refinement and the phase formation were investigated. It was found that mechanical alloying of elemental Ti and Al powders has promotes the formation of Ti(Al) solid solution with great crystallite size refinement. Subsequent heating up to 850oC resulted in a formation of new intermetallic with a dominant TiAl3 phase.